ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI RISK MANAGEMENT DISCLOSURE (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2014) - Sulistyaningsih, Sulistyaningsih; Gunawan, Barbara (Riset Akuntansi dan Keuangan Indonesia, 2016)
This Â study Â was Â to Â analyzeÂ  the Â effect Â of Â management Â ownership, Â public ownership, commissioner size, auditor reputation, leverage and firm size to the risk management dislosure in the annual report. The population in this study is a manufacturing company that listed on indonesia stock exchange in 2012 to 2014. Sampling technique was done by purposive sampling. The number of manufacturing companies that used sampel of 34 companies for a total study sample was 102 annual report. The analytical method used was multiple regression analysis using SPSS 15.0The results of this study indicate that public ownership has significant effect positively and significant degree is 0,041. Commissioner size has significant effect positively and significant Â degreeÂ  0,001. Â WhileÂ  the Â management Â ownership, Â auditor Â reputation, leverage, and firm size didnât have significant effect on risk management disclosure in the annual report..